Understanding Social Participation in Post-stroke Patients: A Phenomenological Study - Praditya, Cahya Lintang Ajeng; Kurnia, Rina (Jurnal Keterapian Fisik, 2025)
Background: Stroke is a leading cause of long-term disability worldwide. Post-stroke patients experience various physical and mental problems. This has a significant impact on the patient’s life, affecting their ability to perform daily activities and participate in community social activities. As many as 50% of post-stroke patients still experience problems with social participation. The purpose of this study was to investigate the social participation of patients after experiencing a stroke. Methods: This research is qualitative research with a phenomenological approach conducted at RSUD by Dr. Soedono Madiun. Data collection was carried out through interviews and documentation of 6 patients who had a stroke for at least 4 months which were included in the purposive sampling criteria. Results: From the thematic analysis that has been carried out, there are three themes regarding the social participation of post-stroke patients: (1) social participation of post-stroke patients, consisting of continuity in social activities, decreased activity, and socialization limitation; (2) social participation barriers, consisting of internal factors and external factors; and (3) coping strategies, consisting of physical recovery, staying connected, and social support. Conclusion: Post-stroke patients experience changes in social participation, they find it difficult to get involved in various social activities due to various barriers from within themselves and their environment. Recommendations for future research are to consider variables that exist as a consideration of research results, such as environmental conditions, stroke severity, gender, and so on.